Concurrent Diabetic Mellitus with Cushing Syndrome in a Dog - Venkatesh, Atmakur; Sumathi, Devaraju; Mohanambal, Kaliyannan; Gupta Kavithakumari, Umesh; Ravi, Ramasamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Cortisol is the principal glucocorticoid released by the adrenals in dogs and cats. Prolonged exposure to inappropriately elevated plasma concentrations of free cortisol leads to devolpment of Cushing’s syndrome or hyperadrenocorticism (HAC) (Rijnberk et al., 2010). HAC is typically a chronic and progressive disease, encountered in middle aged to older dogs. These dogs are usually in a good condition with excellent appetite. The clinical manifestations include polyuria, polydipsia, increased appetite, weight gain, abdominal enlargement, and cutaneous lesion. Laboratory findings include neutrophilia, monocytosis, increased alanine aminotransferase and alkaline phosphatase, increased triglycerides and cholestrol. Screening tests for HAC includes ACTH stimulation test, Low dose dexamethasone suppression test and Urinary cortisol : creatinine ratio. Diagnosis of HAC is confirmed by ultrasonography, Computed Tomography, Magnetic Resonance Imaging (Rijnberk et al., 2010). Laproscopic adrenalectomy is surgical procedure of choice in veterinary medicine or by the use of adrenocorticolytic and adrenocorticostatic drugs (Rijnberk et al., 2010). HAC is occasionally associated with fasting hyperglycemia, overt diabetes mellitus and ketoacidosis. The incidence of DM with HAC in dogs is approximately 16.6-22.0 % (Poppl et al., 2016). The clinical signs for DM are almost common to those of HAC (Polyuria, polydipsia, weight gain, hepatomegaly) (Hess et al., 2000). This communication puts on record a case of concurrent diabetic mellitus with Cushing syndrome in a dog.